Imperial infrastructure and spatial resistance in colonial literature (1880-1930) - Davies, D (2015)
Between 1880 and 1930, the British Empire’s vast infrastructural developments facilitated the incorporation of large parts of the globe into what Immanuel Wallerstein and others have called the capitalist 'world-system'. Colonial literature written throughout this period, in recording this vast expansion, repeatedly cites imperial infrastructures to make sense of the various geographies in which it is set. Physical embodiments of empire proliferate in this writing. Railways and trains, telegraph wires and telegrams, roads and bridges, steamships and shipping lines, canals and other forms of irrigation, cantonments, the colonial bungalow and other kinds of colonial urban architecture—all of these infrastructural lines break up the landscape and give shape to the literature’s depiction and production of colonial space. In order to analyse these physical embodiments of empire in colonial literature, this thesis develops a methodological reading practice called infrastructural reading. Rooted in a dualistic, yet connected use of the word 'infrastructure', this reading strategy works as a critical tool for analysing a mutually sustaining relationship embedded within these literary narratives. It focuses on the infrastructures in the text, both physical and symbolic, in order to excavate the infrastructures of the text, be they geographic, social or economic—namely, the material conditions of the world-system that underpinned Britain's imperial expansion. This methodology is applied to a number of colonial authors including H. Rider Haggard, Olive Schreiner, William Plomer and John Buchan in South Africa and Flora Annie Steel, E.M. Forster, Edmund Candler and Edward Thompson in India. The results show that the infrastructural networks that circulate through colonial fiction are almost always related to some form of anti-imperial resistance, manifestations that include ideological anxieties, limitations and silences, as well as more direct objections to and acts of violent defiance against imperial control and capitalist accumulation. In so doing, the thesis demonstrates how this literary-cultural terrain and the resistance embedded within it has been shaped by, and has in turn shaped, the infrastructure of the capitalist world-system.